Efficient methanol steam reforming over ZnCeZrOx: the unique role of cerium. Issue 23 (2nd November 2022) - Chen, Xuelian; Feng, Zhaochi; Zhao, Dongyuan; Yang, Qihua; Li, Can
Abstract : Zn1 Ce1 Zr9 O x is a ternary solid solution with Zn and Ce doped into the lattice of ZrO2, which is more active and stable than the counterpart without cerium doping in steam reforming of methanol. Abstract : Metal oxide catalysts have been widely used in steam reforming of methanol (SRM), but they face the challenge of long-term running. Herein, we report a ZnCeZrO x catalyst that can operate in SRM stably at 400 °C. The H2 production rates of Zn1 Ce y Zr9 O x catalysts are estimated to be in the range of 103.8 to 109.5 μmolH2 gcat −1 s −1 with methanol conversion rates varying in the range of 93.6% to 99.8% at a WHSV of 4.5 h −1 . The enhanced activity and stability of the ZnZrO x solid solution catalyst is mainly attributed to the large number of oxygen vacancies for water activation and the stable solid solution structure induced by Ce doping. This work indicates that matched rates for H2 O and methanol activation are essential in SRM.